Detection and partial characterization of Cowpea mild mottle virus in mungbean and urdbean by deep sequencing and RT-PCR. (September 2015) - Baranwal, V.K.; Jain, P.; Saritha, R.K.; Jain, R.K.; Gautam, N.K.
Abstract: Urdbean ( Vigna mungo L.) and mungbean ( Vigna radiata L.) are important grain legume crops grown in Asia and Africa. While attempting to identify viruses associated with mungbean and urdbean by next generation sequencing of small RNAs, presence of Cowpea mild mottle virus (CpMMV), a whitefly transmitted virus in diseased samples was detected. This was further confirmed by DAS-ELISA and RT-PCR. A high amount of variability between mungbean and urdbean isolates was observed both in the coat protein (CP) and nucleic acid binding protein (NB) gene sequences. The length of CP gene in both isolates was similar (867 nt) but shared only 90.9% identity at the amino acid level. The NB gene differed in length by seven amino acids and shared sequence identity of 56.4% only at the amino acid level. Our study suggests the presence of distinct strains of CpMMV in India. This is also the first report of CpMMV infecting mungbean and urdbean in India. Highlights: Cowpea mild mottle virus was detected on mungbean and urdbean by next generation sequencing and confirmed by ELISA and RT-PCR. This is the first report of CpMMV infecting mungbean and urdbean in India. A high amount of variability between mungbean and urdbean isolates was observed in the coat protein and nucleic acid binding protein gene ORFs. Our study suggests the presence of distinct strains of CpMMV in India.